THE PROTOTYPE AND DESIGN OF EARLY DETECTION OF GAS LEAKAGE BASED ON MICROCONTROLLER USING PERSONAL EXTREME PROGRAMMING METHOD - Rulin Swastika; Penny Hendriyati; Dwi Agung Cahyadi (Jurnal TAM (Technology Acceptance Model), 2021)
At the beginning of the launch of LPG as an alternative fuel to replace kerosene, many cases of LPGexplosions were caused by gas leaks which were not detected early on. This had created 'anxiety' in the community so that people were reluctant to use LPG due to lack of socialization, lack of public knowledge about dealing with gas leaks and no tools for early detection of gas leaks. Currently, LPG (Liquid Petroleun Gas) in the form of methane gas is widely used by the community after the government launched an energy conversion campaign. Practically today, kerosene has been abandoned by many people and replaced by LPG. The method used in this study uses the PXP (Personal Extreme Programming) method with single programming. Complete collection of information data allows developers to find views to create a software so that it can be right on target. This stage requires several steps, planning, design, coding, system testing. The goal is to produce a useful tool which can be used by the wider community. This tool can detect gas leaks precisely if the sensor is heated and the gas source is not mixed with free air. This tool can send a signal in the form of an SMS warning automatically and can sound an alarm so that people around who hear the alarm can know.